Design of diversion weirs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Design of diversion weirs: small scale irrigation in hot climates by Rozgar Baban 1995 228pp ISBN 0 471 95211 7 (Pbk)